Hormonal imbalance in brinjal tissues infected with little leaf phytoplasma - D.K. MITRA, A.K. DAS* and (Indian Phytopathology, 2002)
Little leaf infection of brinjal has increased the levels of indole-3- acetic acid (IAA) and cytokinin contents in all the infected tissues as compared to the healthy controls except in infected leaves which showed lower cytokinin activity.